CORPORATE BANKRUPTCY UNDER THE LEGISLATION OF KAZAKHSTAN: PROBLEMS AND SOLUTIONS - Veselskaya Natalia Romanovna; Akan Maral Rymkhankyzy (Foundations and Trends in Modern Learning, 2025)
Corporate bankruptcy is the most important institution of the market economy, allowing economically unviable firms to either liquidate or reorganize, protect creditors’ rights and effectively redistribute resources. This serves as a guarantee of financial discipline, ensuring that business failures do not lead to systemic instability. Well-designed bankruptcy systems ensure fair treatment of both debtors and creditors, promote the recycling of capital for more productive use, and ultimately contribute to a more sustainable and transparent business environment. Despite significant progress in legislation over the past decade, primarily due to the Entrepreneurial Code of the Republic of Kazakhstan (2015) and subsequent amendments to the Law on Rehabilitation and Bankruptcy, the practical implementation of insolvency procedures remains ineffective.